Hubungan Mutu Pelayanan Kefarmasian dengan Kepuasan Pasien di Apotek Wilayah Kecamatan X Kota Surakarta Tahun 2022: Correlation of Quality of Pharmaceutical Services and Patient Satisfaction in Pharmacy of X District Surakarta in 2022 - Zorathea Benita; Tri Wijayanti; Ganet Eko Pramukantoro (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Pharmaceutical service quality refers to degree of service perfection that increases patient satisfaction. Pharmacies are required to review several aspects in order to improve quality of pharmaceutical services which include tangibles, empathy, assurance, responsiveness and reliability. The research objective was to determine the correlation between quality of pharmaceutical services and degree of patient satisfaction with pharmaceutical services in pharmacy of X District Surakarta in 2022. This study is a descriptive involved 225 patients and 8 pharmacies in a survey. Pharmaceutical service data is concluded based on quality category of pharmaceutical services in pharmacies. Patient satisfaction was analyzed by comparing the weight of reality and expectations based on variables that affect patient satisfaction. Additionally, it was examined using the SPSS 23 Spearsman's Rho test to see if there was a correlation between caliber of pharmaceutical services and degree of patient satisfaction. In pharmacies of X District Surakarta, the quality of pharmaceutical services received an average score of 63,62% (sufficient) and an average percentage of patient satisfaction levels of 79.55% (satisfied) in 2022. The results of the Spearman's rho correlation test of 0.994 indicate that there is a correlation between quality of pharmaceutical services and level of patient satisfaction. Keywords: pharmaceutical services, patient satisfaction, pharmacy X district, Surakarta Abstrak Mutu pelayanan kefarmasian mengacu pada tingkat kesempurnaan suatu pelayanan untuk meningkatkan kepuasan pasien. Pihak apotek wajib meninjau aspek meliputi bukti fisik, empati, jaminan, daya tanggap dan reliabilitas. Tujuan penelitian ini adalah untuk mengetahui hubungan mutu pelayanan kefarmasian dengan tingkat kepuasan pasien terhadap pelayanan kefarmasian di apotek wilayah Kecamatan X Kota Surakarta tahun 2022. Penelitian ini merupakan penelitian deskriptif dengan metode survei menggunakan kuesioner terhadap 8 apotek dan 225 pasien. Data pelayanan kefarmasian disimpulkan berdasarkan kategori mutu pelayanan kefarmasian di apotek. Kepuasan pasien dianalisis dengan membandingkan bobot realita dan ekspektasi berdasarkan variabel yang mempengaruhi kepuasan pasien. Selanjutnya dianalisis untuk mengetahui ada atau tidaknya hubungan antara mutu pelayanan kefarmasian dengan tingkat kepuasan pasien menggunakan SPSS 23 uji spearsman’s rho. Mutu pelayanan kefarmasian di apotek wilayah Kecamatan X Kota Surakarta tahun 2022 memperoleh skor rata-rata sebesar 63,62% (cukup) dan rata- rata persentase tingkat kepuasan pasien sebesar 79,55 % (puas). Hasil uji korelasi spearman’s rho sebesar 0,994 hal tersebut menunjukkan bahwa terdapat hubungan antara mutu pelayanan kefarmasian dengan tingkat kepuasan pasien. Kata Kunci: pelayanan kefarmasian, kepuasan pasien, apotek Kecamatan X Surakarta